Pengaruh Kepemimpinan, Motivasi Dan Disiplin Terhadap Kinerja : Study Kasus Hotel NEO, Kebayoran Jakarta - Zainuddin Siata; Heri Sasono (STIKes Ibnu Sina Ajibarang, 2024)
Employee performance must always be maintained so that the company survives. Research to determine the influence between variables of Leadership, Motivation and Work Discipline on Employee Performance at NEO Hotel, Kebayoran, Jakarta. This research method uses quantitative research methods by conducting parametic statistical analysis in the form of multiple linear regression analysis. The data used is primary data obtained from the answers of 40 respondents.The results showed that leadership and motivation had a significant effect partially and simultaneously all of them had a significant effect on employee performance and the correlation value was 75.4% and the remaining 24.6% was found in other factors that were not studied.